Penguatan Keterlibatan Remaja Melalui Pendekatan Komunikasi Partisipasif Pada Program Posyandu - oktarvianto, cheriasa putri kasih; Satriya, Candra Yudha (Universitas Muhammadiyah Magelang, 2026)
Adolescent involvement in Posyandu activities is still relatively low, even though their role is important in supporting the sustainability of community-based health programs. This study aims to analyze the strengthening of adolescent involvement through a participatory communication approach in the Posyandu Remaja Melati 6 program. This research uses a qualitative method with a descriptive approach. Data were collected through in-depth interviews and documentation involving Posyandu cadres, adolescents, and program managers. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, with source triangulation to ensure data validity. The results of the study indicate that participatory communication plays a role in increasing adolescent involvement through open communication, providing space for active participation, and the use of media that are appropriate to the characteristics of the younger generation. In addition, dialogic and collaborative communication processes encourage a sense of ownership and awareness among adolescents about the importance of Posyandu. The findings of this study confirm that participatory communication functions not only as an information delivery strategy but also as an empowerment process that can increase active adolescent participation in community health programs.